2018
DOI: 10.1002/ajb2.1052
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐locus phylogenetics, lineage sorting, and reticulation in Pinus subsection Australes

Abstract: Our analyses document cytonuclear discordance in Pinus subsection Australes. We attribute this discordance to ancient and recent introgression and present a phylogenetic hypothesis in which mostly hierarchical relationships are overlain by gene flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 76 publications
2
34
0
1
Order By: Relevance
“…These results add to the growing number of studies that have formally evaluated the role of introgression in generating phylogenetic incongruence between plant nuclear and organellar genomes (e.g. Winkler et al ., ; Folk et al ., ; García et al ., ; Morales‐Briones et al ., ; Gernandt et al ., ). What has emerged is the robust detection of cytoplasmic introgression in diverse taxa representing both angiosperms and gymnosperms.…”
Section: Discussionmentioning
confidence: 97%
“…These results add to the growing number of studies that have formally evaluated the role of introgression in generating phylogenetic incongruence between plant nuclear and organellar genomes (e.g. Winkler et al ., ; Folk et al ., ; García et al ., ; Morales‐Briones et al ., ; Gernandt et al ., ). What has emerged is the robust detection of cytoplasmic introgression in diverse taxa representing both angiosperms and gymnosperms.…”
Section: Discussionmentioning
confidence: 97%
“…DNA was quantified with a Qubit fluorometer kit (Life Technologies, Carlsbad, CA, USA) and shipped to Arbor Biosciences (Ann Arbor, MI, USA) for preparation of genomic libraries, and enrichment of low copy nuclear DNA genes using the combined target capture and genome skimming Hyb‐Seq method (Weitemier et al., ). A more detailed description of DNA extraction and sequencing methods is described elsewhere (Gernandt et al., ). Sequences were generated with an Illumina HiSeq 2000 (San Diego, CA, USA) with 100‐bp paired‐end reads.…”
Section: Methodsmentioning
confidence: 99%
“…The high degree of introgression can be explained by the relatively recent diversification of species in the subsection Australes and the very weak reproductive barriers between them (Little & Righter, 1965;Garrett, 1979;Dvorak et al, 2000;Vargas-Mendoza et al, 2011;Gernandt et al, 2018). Similar weak reproductive barriers and high recent speciation rates have been recorded for madrones (Arbutus spp.)…”
Section: Discussionmentioning
confidence: 73%
“…Natural hybridization has also been observed in other Mexican pine species (Gernandt et al, 2018). Previous studies of the subsection Australes identified natural hybridization between P. oocarpa × Pinus caribaea and P. oocarpa × Pinus pringlei only by morphological traits (Styles & Stead, 1982;López-Upton et al, 2001).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation